FRAGMENTED IDENTITIES IN ANDRIC’S SHORT STORIES - Branka Brlenić-Vujić; Tamara Damjanović (Hum, 2012)
Through the title topic authors analyze the issue of identity in Andric’s paradigmatic short stories. Fragmentation of identities is manifested in relation to the other in searching for completeness. At the same time they tried to throw light upon role of fluid identities which like bridges connect distant coasts.